The effect study of air temperature on the thermal performance of gas-turbine unit at Zawia power plant - Wesam M. Esharif; Basmah A. Aldeeb; Mohammed Q. Bahmi (African Journal of Advanced Pure and Applied Sciences, 2025)
In this paper, the thermal performance of a gas turbine unit at Zawia combined cycle power plant was evaluated for the months of January and June, to determine the extent to which it is affected by the ambient air temperature. The 25% mist water injection technology was used in this plant to verify its effectiveness in enhancing the thermal performance of June by cooling the air entering the compressor. The thermal performance of the plant for the month of June was also compared before and after using the fogging water injection technique. Initially, some thermodynamic variables were calculated, including: thermal efficiency, total electrical efficiency, and exhaust gas flow rate, based on the average ambient air temperatures for the months of January and June, 16oC and 45oC, respectively. The results indicate that the thermal efficiency and total electrical efficiency of the unit increase with decreasing air temperature; In January, they reached 39.8% and 36.2%, respectively, while in June they reached 39.15% and 28.76%, respectively. The results showed that using Fogging technology in the summer (June) enhances the thermal performance -power generation and the efficiency- of the gas turbines unit. It is clear from the data measured for June that the use of the fogging cooling system leads to an increase in the overall electrical efficiency of the unit by 5.24%, a decrease in the specific fuel consumption (S.F.C.) by 0.048kg/kw.hr, and the net-work (Wnet) of kJ/kg is 6.3. Also, the decrease in the compressor inlet temperature from 318.15K to 301.6K leads to a decrease in the outlet temperature from 716K to 687K, which is a decrease of 4.1%.